Measurements and improvements of the response of the PANDA-EMC prototype PROTO 60 to high energetic particles and photons in accelerator experiments - Moritz, Markus; Justus Liebig University Giessen (My University, 2013)
The PANDA experiment at FAIR will provide an opportunity to achieve a betterunderstanding of complex hadronic systems. Measurements will be performed withantiprotons using a fixed-target setup. In order to reconstruct most of the reactions, a precise measurement of electromagnetic probes and their energies are crucial. An important and major component of the detector is therefore the electromagnetic calorimeter. Due to the lack of commercial availability of such ambitious, complex and highly specialized detector systems, detailed research and development are nec essary, including prototype development, testing and optimization. The investigation of the response of a homogeneous electromagnetic calorimeter prototype is the main scope of the present thesis. This prototype, called PROTO 60, is composed out of 60 truncated pyramidal shaped PWO-II crystals, cooled down to -25 C and read out with one LargeArea Avalanche Photodiode (LAAPDs). The PROTO 60 represents a small section ofthe central barrel part of the PANDA calorimeter. Its response is being investigated for the first time over an extensive energy range from 52.34 MeV up to 15 GeV within several experiments measuring the response to energy marked photons or positrons at the highest energy, respectively. The study verified the principle detector concept. A linear response was observed. The achieved overall resolution can be parameterized as:sigma/E= sqrt((1,86%/sqrt(E/GeV))^2+(0,25%/(E/GeV))^2+(1,46%)^2)Due to the use of only one single LAAPD per crystal with the effective surface of 1 cm2 and a not linearized light collection within the crystals, these parameters represent an upper performance limit of the final PANDA calorimeter. A detailed GEANT based model of the prototype was developed in order to investigate the calibration based on cosmic radiation or a 150 GeV muon beam and to understand the impact of the detailed geometry and light collection on the achieved performance.Furthermore, the influence of the APD gain on the energy resolution was examinedwith a light pulser system. The performed measurements revealed that a gain of 50, as used for the CMS electromagnetic calorimeter, does not apply for the PANDA electromagnetic calorimeter in particular in the low energy regime.

Das PANDA-Experiment bei FAIR stellt eine Möglichkeit dar, ein besseres Verständnis von komplexen hadronischen Systemen zu erlangen. Die Messungen werden mit Hilfe von Antiprotonen in einem Fixed-Target-Experiment durchgeführt. Für die Rekonstruktion der meisten Reaktionen ist ein genauer Nachweis von elektromagnetischen Proben sowie die Messung ihrer Energien entscheidend. Aufgrund dessen ist das elektromagnetische Kalorimeter eine wichtige Komponente des PANDA Detektors. Generell sind solche anspruchsvollen, komplexen und hoch spezialisierten Detektorsysteme nicht kommerziell erhältlich. Für dessen Realisierung sind somit umfangreiche Forschungsarbeiten nötig, welche unter anderem die Entwicklung, das Testen sowie die Optimierung von Prototypen beinhalten. Die Hauptzielsetzung dieser Arbeit ist die Untersuchung des Ansprechverhaltens des Prototypen eines homogenenelektromagnetischen Kalorimeters. Dieser Prototyp wird als PROTO 60 bezeichnetund besteht aus 60 pyramidenstumpfförmigen PWO-II Kristallen welche auf -25 Cgekühlt und jeweils mit einer Large-Area-Avalanche Photodiode (LAAPD) ausgelesenwerden. Er repräsentiert einen kleinen zentralen Ausschnitt aus dem fassförmigen Teil des PANDA Kalorimeters. Im Rahmen mehrerer Experimente wurde zum ersten mal sein Ansprechen über einen umfangreichen Energiebereich von 52 MeV bis 15 GeV mittels energiemarkierten Photonen bzw. Positronen für die höchste Energie, untersucht. Es konnte gezeigt werden, dass dieser Detektorprototyp prinzipiell funktioniert und linear auf Photonen anspricht. Die erzielte Energieauflösung über den kompletten gemessenen Energiebereich kann durch sigma/E= sqrt((1,86%/sqrt(E/GeV))^2+(0,25%/(E/GeV))^2+(1,46%)^2)parametrisiert werden. Aufgrund der Verwendung von nur einer 1 cm2 grossen LAAPDpro Kristall und einer nicht linearisierten Lichtsammlung stellen die erzielten Ergebnisse lediglich eine obere Grenze für die Energieauflösung dar. Ein detailliertes Simulationsmodell des Prototypen wurde in GEANT 4 erstellt um dessen Kalibration mittels kosmischer Strahlung und eines 150 GeV Myonenstrahls zu untersuchen, sowie den Einfuss der komplexen Geometrie und der Lichtsammlung auf dessen Ansprechen. Ferner wurde mittels eines Lichtpulsers der Einfluss der APD Verstärkung auf die Energieauflösung untersucht. Insbesondere für niedrige Energien zeigte sich, dass ein Verstärkungsfaktor von 50, welcher von dem elektromagnetischen Kalorimeter des CMS Detektors verwendet wird, nicht optimal ist.
Messungen und Optimierungen des Ansprechens des PANDA-EMC Prototypen PROTO 60 auf hoch energetische Partikel und Photonen in Beschleunigerexperimenten
Keywords: Kalorimeter; PANDA; Energieauflösung; PROTO 60; Prototyp; Calorimeter; Energyresolution; Calibration; GEANT; Cosmic Radiation; ddc:530